Effect of Ba-Substitution at Sr-Site on the Structural and Dielectric Characteristics of SrMnO3 - Amir, M.; Atiq, S.; Riaz, S.; Naseem, S. (The Nucleus, 2015)
Antiferromagnetic Ba substituted SrMnO3 has a perovskite structure with a B-site magnetic ion which gives higher magnetic ordering temperatures. Ferroelectric transitions in these perovskites have been observed due to off centering of Mn4+ ions. In this work, we report synthesis of Sr1-xBaxMnO3 (x= 0.2, 0.4, 0.6 and 0.8) samples using sol-gel auto-ignition method. The prepared samples were sintered at 1000 ÂºC for 4 hours each which ultimately led to the development of the perovskite structure, as determined by X-ray diffraction. The crystallite size was determined by using Scherrerâ€™s formula. Frequency dependent dielectric characteristics have been investigated systematically using an impedance analyzer. These studies reveal the decreasing dielectric behavior if the concentration of Ba is increased.